Evaluasi Pemeriksaan Ultrasonografi Leher dengan Klinis Limfadenopati pada Bagian Submental: Evaluation of Neck Ultrasonography Examination with Clinical Lymphadenopathy in the Submental Region - Pratama, Ziko; Fransiscus Herianto; Tiara Rahmadhini (MPI Press, 2024)
Introduction: Head and neck cancers are among the most lethal, with nasopharyngeal cancer being prominent. According to WHO (2015), these cancers rank sixth globally and fourth in Indonesia. Approximately 70% of nasopharyngeal cancer cases begin with enlarged lymph nodes. Data from the Indonesian Doctors Association (IDI) in 2017 indicate that 56% of lymph node cases occur in adults, often without clinical symptoms. Objective: This study aims to describe the examination procedures, scanning techniques, and sonographic findings of lymphadenopathy in the submental region at Mayapada Hospital. Method: A descriptive qualitative study was conducted through direct observation from November 2024 to January 2025 at Mayapada Hospital, Jakarta. The sample consisted of one patient who underwent neck ultrasound focused on the submental area. Data were collected and analyzed qualitatively. Result: The patient underwent a scheduled neck ultrasound using a 7–12 MHz linear transducer. No special preparation was required. Imaging involved three transverse and three longitudinal views, focusing exclusively on the submental region. The sonographic findings revealed lymphadenopathy characterized by an oval shape, regular margins, and a visible hilum. Conclusion: The study outlines the standardized procedures for submental ultrasonography in identifying lymphadenopathy at Mayapada Hospital. Minimal preparation is needed, and the technique provides clear imaging features that support diagnosis.